2019
DOI: 10.1002/ijc.32512
|View full text |Cite
|
Sign up to set email alerts
|

Familial aggregation of early‐onset cancers

Abstract: This registry‐linkage study evaluates familial aggregation of cancer among relatives of a population‐based series of early‐onset (≤40 years) cancer patients in Finland. A cohort of 376,762 relatives of early‐onset cancer patients diagnosed between 1970 and 2012 in 40,538 families was identified. Familial aggregation of early‐onset breast, colorectal, brain and other central nervous system (CNS) cancer and melanoma was explored by standardized incidence ratios (SIR), stratified by relatedness. Gender‐, age‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…Our findings also confirm and strengthen the evidence of common familial risks for childhood CNS tumours and leukaemia, and are consistent with a wide range of studies 44,45,46,47 The biological mechanisms behind the associations found in the present study might be explained by genetic and environmental factors or interaction between them. However, studies conducted in first-degree relatives suffer from inability to discern between possible environmental effects or shared genetic susceptibility.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also confirm and strengthen the evidence of common familial risks for childhood CNS tumours and leukaemia, and are consistent with a wide range of studies 44,45,46,47 The biological mechanisms behind the associations found in the present study might be explained by genetic and environmental factors or interaction between them. However, studies conducted in first-degree relatives suffer from inability to discern between possible environmental effects or shared genetic susceptibility.…”
Section: Discussionsupporting
confidence: 93%
“…Follow‐up ended either at the date of first diagnosis of childhood and young adult (ChYA) cancer, attainment of age 40 years, date of emigration or death, or December 31, 2016, whichever came first. The identification of family members and follow‐up for both family members and probands has been described previously 20 …”
Section: Methodsmentioning
confidence: 99%
“…Another cohort that can be approached to test this hypothesis are those patients with familial clustering, in whom inherited genetic susceptibility has been ruled out. Two such cohorts have been identified in Scandinavia ( 107 , 108 ). The cohort of patients with breast cancer in the study by Heikkinen et al ( 107 ) is a perfect example of a testable study group.…”
Section: Testing the Hypothesis And Its Implicationsmentioning
confidence: 99%
“…Two such cohorts have been identified in Scandinavia ( 107 , 108 ). The cohort of patients with breast cancer in the study by Heikkinen et al ( 107 ) is a perfect example of a testable study group.…”
Section: Testing the Hypothesis And Its Implicationsmentioning
confidence: 99%